Recycling Of Clay Based Demolition Wastes For The Production Of Concrete Block. - Ummi Kalsum, Ummi Kalsum; N, H M; Mashitah, Mashitah; M.D, M.D; Badorul, Badorul; A.B, A.B (2008)

(untitled)
Construction and Demolition (C & D) wastes constitute a major portion of total solid wastes production in the world, and most of them are disposed in land fills. Preservation of the environment and conservation of the rapidly diminishing natural resources be the essence of sustainable development.